ASSOCIATIONS BETWEEN MATERNAL INTERACTION BEHAVIOR, MATERNAL PERCEPTION OF INFANT TEMPERAMENT, AND INFANT SOCIAL WITHDRAWAL. Issue 6 (1st October 2013) - Puura, Kaija; Mäntymaa, Mirjami; Leppänen, Jukka; Peltola, Mikko; Salmelin, Raili; Luoma, Ilona; Latva, Reija; Tamminen, Tuula
ABSTRACT Infant social behavior develops in the context of early parent–infant interaction. Persisting withdrawal from social interaction is a sign of infant distress and is linked with the existence of risk factors. Impaired social behavior of the infant not only may be an indicator of pathology in the infant but the first sign of an effect of a psychosocial risk. In this study, we assessed 39 seven‐month‐old infants in videotaped interaction with their mothers and then compared the total score of the infant social behavior rated with the Alarm Distress Baby Scale (ADBB; A. Guedeney & A. Fermanian, 2001) with variables of mother–infant interaction rated with the Emotional Availability Scales, second edition (EAS 2; Z. Biringen, J. Robinson, & R.N. Emde, 2000). The ADBB total score had a strong negative correlation with maternal sensitivity in the EAS 2 (r = −0.75) and with the EAS 2 child variables of child involvement (r = 0.82) and child responsiveness (r = 0.85), indicating that the infants with more signs of social withdrawal had less sensitive mothers and were less involving and responsive in the interaction. Against our expectations, the ADBB total score had no correlation with maternal structuring. Our results give further support of the ability of the ADBB to screen for early signs of pathology in infant social behavior and problems in parent–infant interaction.